A data-assimilated SEAS5 forecasting framework for seasonal hydropower inflows in a snow-dominated basin - Gökçen Uysal; Marie-Amélie Boucher; Charles Mathieu; Rodolfo Alvarado-Montero; Ali Arda Şorman (Journal of Hydrology, 2026)

The modulatory effects of Cyberlindnera jadinii on growth performance, health, welfare, and product quality of Atlantic salmon (Salmo salar): A large-scale field experiment - Jamie M. Hooft; Sérgio D.C. Rocha; Ruth Montero; Byron Morales-Lange; Kathiresan Purushothaman; Brankica Djordjevic; Monica Juarez Ceballos; Mathieu Castex; IIdar Nisamedtinov; Charles McLean Press; Liv Torunn Mydland; Margareth Øverland (Aquaculture, 2026)

Mineralogical and geochemical evolution of the lateritic weathering profile on the Nyambaka basalt, Adamawa-Cameroon: implication to bauxitization process - Marie Alex Akaba Chimeu; Calistus Gentry Fuh; Alex Fotso Kengne; Mathieu Nouazi Momo; Rose Yongue-Fouateu; Charles Nkoumbou (Arabian Journal of Geosciences, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark; Valentin Thomas; Richard S. Taylor; Mathieu Charles; Audrey Laurent; Isabelle Schwartz-Cornil; Bertrand Collet; Delphine Lallias; Daniel J. Macqueen; Samuel A.M. Martin; Pierre Boudinot (Fish & Shellfish Immunology, 2025)

Population Genomics of Incipient Allochronic Divergence in the Pine Processionary Moth - Tanguy Muller; Mathieu Gautier; Éric Lombaert; Raphaël Leblois; Laure Sauné; Manuela Branco; Carole Kerdelhué; Charles Perrier (Molecular Ecology, 2025)
Allochronic divergence is a key evolutionary mechanism that can frequently lead to incipient speciation. Although theoretical models suggest that such divergence is notably facilitated by small population size and genetic polymorphisms influencing reproductive timing, though constrained by genetic load, empirical validation remains limited. We investigated these predictions by re‐analysing a case of allochronic differentiation between two sympatric populations of pine processionary moth ( Thaumetopoea pityocampa ) in Portugal, using whole genome resequencing (IndSeq and PoolSeq) of those two populations and eight allopatric ones. We inferred the demographic history of those populations, assessed their genetic load and searched for genomic regions associated with life cycle differences. Our analyses revealed a recent split between the sympatric allochronic populations, accompanied by a strong reduction in gene flow, bottlenecks, inbreeding and accumulation of deleterious variants. Genome scans identified several loci associated with life cycle variation, including genes putatively involved in circadian rhythm regulation, predominantly located on the Z chromosome. We discuss how these empirical genomic findings support theoretical expectations that assortative mating driven by differences in reproductive timing, underpinned by polymorphisms in circadian genes, along with genetic drift and purge of genetic load at high‐impact sites, can promote the onset and persistence of allochronic divergence.

Chlorophyll shading reduces zooplankton diel migration depth in a high-resolution physical–biogeochemical model - Mathieu A. Poupon; Laure Resplandy; Jessica Garwood; Charles Stock; Niki Zadeh; Jessica Y. Luo (Ocean Science, 2025)
Zooplankton diel vertical migration (DVM) is critical to ocean ecosystem dynamics and biogeochemical cycles, by supplying food and injecting carbon into the mesopelagic ocean (200–800 m). The deeper the zooplankton migrate, the longer the carbon is sequestered away from the atmosphere and the deeper the ecosystems they feed. Sparse observations show variations in migration depths over a wide range of temporal and spatial scales. A major challenge, however, is to understand the biological and physical mechanisms controlling this variability, which is critical for assessing impacts on ecosystem and carbon dynamics. Here, we introduce a migrating zooplankton model for medium and large zooplankton that explicitly resolves diel migration trajectories and biogeochemical fluxes. This model is integrated into the MOM6-COBALTv2 ocean physical–biogeochemical model and is applied in an idealized high-resolution (9.4 km) configuration of the North Atlantic. The model skillfully reproduces observed North Atlantic migrating zooplankton biomass and DVM patterns. Evaluation of the mechanisms controlling zooplankton migration depth reveals that chlorophyll shading decreases zooplankton migration depths by 60 m in the subpolar gyre compared with the subtropical gyre, with pronounced seasonal variations linked to the spring bloom. Fine-scale spatial effects (

The impact of exercise timing on energy intake: A systematic review and meta-analysis of diurnal and meal timing effects - Capucine Guédet; Sémah Tagougui; Alexandre-Charles Gauthier; David Thivel; Marie-Eve Mathieu (Appetite, 2025)

Complementary classifications of aeolian dunes based on morphology, dynamics, and fluid mechanics - Sylvain Courrech du Pont; David M. Rubin; Clément Narteau; Mathieu G.A. Lapôtre; Mackenzie Day; Philippe Claudin; Ian Livingstone; Matt W. Telfer; Jani Radebaugh; Cyril Gadal; Andrew Gunn; Patrick A. Hesp; et al. (Earth-Science Reviews, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Deciphering microbial communities of three Savoyard raw milk cheeses along ripening and regarding the cheese process - Cresciense Lecaudé; Nicolas Orieux; Sarah Chuzeville; Alicia Bertry; Eric Coissac; Frederic Boyer; Aurélie Bonin; Nelly Colomb-Boeckler; Bruno Mathieu; Manon Recour; Joël Vindret; Céline Pignol; et al. (International Journal of Food Microbiology, 2024)

Estimating the relationship between EROI and profitability of oil sands mining, 1997–2016 - Charles Guay-Boutet; Mathieu Dufour (Ecological Economics, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Deep behavioral impairment in the pearl oyster Pinctada radiata exposed to anthropogenic noise and light stress - Mohcine Charifi; Razan Khalifa; Bruno W. Giraldes; Mohamedou Sow; Zainab Hizam; Mathieu Carrara; Eric Maneux; Shafeeq Hamza; Anne Bassères; Philippe Blanc; Alexandra Leitão; Jean-Charles Massabuau (Frontiers in Marine Science, 2023)
The pearl oyster Pinctada radiata is an iconic species in the Arabian Gulf, which is one of the ecosystems most at risk in the world because of the multiple sources of pollution it faces. Alongside chemical pollution, the Gulf is ranked first with regard to noise and light pollution, and pearl oyster populations are at risk. The impact of these latter types of pollution on marine invertebrates is still poorly known. We used the difference in noise and brightness that can exist between a very quiet room without artificial lighting and a standard laboratory room equipped with a standard aquarium as a testbed to explore the possible impact of noise and light pollution on the behavioral and biological traits of Pinctada radiata without added chemical exposure. During an experiment that lasted 2.5 months, we analyzed their grouping behavior, valve activity, biological rhythm, growth rate and spawning activity. In the standard aquarium kept in the laboratory room, the oysters dispersed instead of regrouping as in their natural environment, regrouping which was observed in the quiet room. They stayed closed longer, the opening amplitude of their valves was systematically lower, and in the closed position, they squeezed their valves more tightly when subjected to noise and light pollution. Their daily opening rhythm was strongly structured by switching the electric light on and off, and females showed significantly less egg-laying behavior. In conclusion, seemingly innocuous human activities can lead to very significant alterations in pearl oyster behavior. We propose that it could have significant effects on populations and ecosystems.

Cognitive and behavioral effects of whole brain conventional or high dose rate (FLASH) proton irradiation in a neonatal Sprague Dawley rat model - Michael Williams; Chiho Sugimoto; Samantha Regan; Emily Pitzer; Adam Fritz; Mathieu Sertorio; Anthony Mascia; Ralph Vatner; John Perentesis; Charles Vorhees (Neurotoxicology and Teratology, 2023)

Hydrogeochemical processes of critical zone developed in Tégulines Clay, Paris Basin: Hydrogeochemical and multi-isotopic approach (δ13C, δD, δ18O, 87Sr/86Sr and 14C) - Catherine Lerouge; Mathieu Debure; Ana-Maria Fernández; Philippe Négrel; Benoit Madé; Nicolas Maubec; Christine Fléhoc; Catherine Guerrot; Michaela Blessing; Benoit Henry; Jean-Charles Robinet (Journal of Hydrology, 2023)

The ID NOW COVID-19, a high-speed high-performance assay - Eric Farfour; M. Asso-Bonnet; M. Vasse; Emilie Catherinot; Colas Tcherakian; Antoine Magnan; Simon Chauveau; Sylvie Colin de Verdière; Hélène Salvatore; Antoine Roux; Benjamin Zuber; Charles Cerf; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Population, Temperature and Feeding Rate Effects on Individual Feed Efficiency in European Sea Bass (Dicentrarchus labrax) - Charles Rodde; Marc Vandeputte; François Allal; Mathieu Besson; Frédéric Clota; Alain Vergnet; John A. H. Benzie; Hugues de Verdal (Frontiers in Marine Science, 2020)

Identification of two new trichome-specific promoters of Nicotiana tabacum - Mathieu Pottier; Raphaëlle Laterre; Astrid Van Wessem; Aldana M. Ramirez; Xavier Herman; Marc Boutry; Charles Hachez (Planta, 2020)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Chemical composition of the essential oils from the aerial parts of two Malagasy endemic species (Apiaceae): Billburttia capensoides Sales & Hedge and Billburttia vaginoides Sales & Hedge - Stephan R. Rakotonandrasana; Delphin J. R. Rabehaja; Mathieu Paoli; Dominique de Rocca Serra; Charles Andrianjara; Ange Bighelli; Panja A. R. Ramanoelina; Félix Tomi (Natural Product Research, 2019)

A genomic map of climate adaptation in Mediterranean cattle breeds - Laurence Flori; Katayoun Moazami‐Goudarzi; Véronique Alary; Abdelillah Araba; Ismaïl Boujenane; Nadjet Boushaba; François Casabianca; Sara Casu; Roberta Ciampolini; Armelle Coeur D'Acier; Corinne Coquelle; Juan‐Vicente Delgado; et al. (Molecular Ecology, 2019)
Domestic species such as cattle ( Bos taurus taurus and B. t. indicus ) represent attractive biological models to characterize the genetic basis of short‐term evolutionary response to climate pressure induced by their post‐domestication history. Here, using newly generated dense SNP genotyping data, we assessed the structuring of genetic diversity of 21 autochtonous cattle breeds from the whole Mediterranean basin and performed genome‐wide association analyses with covariables discriminating the different Mediterranean climate subtypes. This provided insights into both the demographic and adaptive histories of Mediterranean cattle. In particular, a detailed functional annotation of genes surrounding variants associated with climate variations highlighted several biological functions involved in Mediterranean climate adaptation such as thermotolerance, UV protection, pathogen resistance or metabolism with strong candidate genes identified (e.g., NDUFB3 , FBN1 , METTL3 , LEF1 , ANTXR2 and TCF7 ). Accordingly, our results suggest that main selective pressures affecting cattle in Mediterranean area may have been related to variation in heat and UV exposure, in food resources availability and in exposure to pathogens, such as anthrax bacteria ( Bacillus anthracis ). Furthermore, the observed contribution of the three main bovine ancestries (indicine, European and African taurine) in these different populations suggested that adaptation to local climate conditions may have either relied on standing genomic variation of taurine origin, or adaptive introgression from indicine origin, depending on the local breed origins. Taken together, our results highlight the genetic uniqueness of local Mediterranean cattle breeds and strongly support conservation of these populations.

Natural hazards in Goma and the surrounding villages, East African Rift System - Charles M. Balagizi; Antoine Kies; Marcellin M. Kasereka; Dario Tedesco; Mathieu M. Yalire; Wendy A. McCausland (Natural Hazards, 2018)

Harnessing genetic resources and progress in plant genomics for fonio (Digitaria spp.) improvement - Mathieu Anatole Tele Ayenan; Kpedetin Ariel Frejus Sodedji; Charles Ikenna Nwankwo; Katina Floride Olodo; Mahulé Elysé Boris Alladassi (Genetic Resources and Crop Evolution, 2018)

Soil temperature and CO2 degassing, SO2 fluxes and field observations before and after the February 29, 2016 new vent inside Nyiragongo crater - Charles M. Balagizi; Mathieu M. Yalire; Honoré M. Ciraba; Vicky B. Kajeje; Abel S. Minani; Annie B. Kinja; Marcellin M. Kasereka (Bulletin of Volcanology, 2016)

In vivo phosphorylation of a peptide tag for protein purification - Marine Goux; Amina Fateh; Alain Defontaine; Mathieu Cinier; Charles Tellier (Biotechnology Letters, 2016)

Detailed multidisciplinary monitoring reveals pre- and co-eruptive signals at Nyamulagira volcano (North Kivu, Democratic Republic of Congo) - Benoît Smets; Nicolas d’Oreye; François Kervyn; Matthieu Kervyn; Fabien Albino; Santiago R. Arellano; Montfort Bagalwa; Charles Balagizi; Simon A. Carn; Thomas H. Darrah; José Fernández; Bo Galle; et al. (Bulletin of Volcanology, 2014)

Engineering of a phosphorylatable tag for specific protein binding on zirconium phosphonate based microarrays - Mathieu Cinier; Marc Petit; Frédéric Pecorari; Daniel R. Talham; Bruno Bujoli; Charles Tellier (JBIC Journal of Biological Inorganic Chemistry, 2012)

A new pear scab resistance gene Rvp1 from the European pear cultivar ‘Navara’ maps in a genomic region syntenic to an apple scab resistance gene cluster on linkage group 2 - Lydie Bouvier; Marie Bourcy; Mathieu Boulay; Marie Tellier; Philippe Guérif; Caroline Denancé; Charles-Eric Durel; Yves Lespinasse (Tree Genetics & Genomes, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)